2014
DOI: 10.1002/jlcr.3233
|View full text |Cite
|
Sign up to set email alerts
|

A novel radiochemical approach to 1‐(2'‐deoxy‐2'‐[18F]fluoro‐β‐d‐arabinofuranosyl)cytosine (18F‐FAC)

Abstract: F-FAC (1-(2'-deoxy-2'-[ F]fluoro-β-D-arabinofuranosyl)-cytosine) is an important 2'-fluoro-nucleoside-based PET tracer that has been used for in vivo prediction of response to the widely used cancer chemotherapy drug gemcitabine. Previously reported synthetic routes to 18 F-FAC have relied on early introduction of the 18 F radiolabel prior to attachment to protected cytosine base. Considering the 18 F radiochemical half-life (110 minutes) and the technical challenges of multi-step syntheses on PET radiochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The tracer was produced with high chemical and radiochemical purity with late-stage radio-fluorination of the pyrimidine. However, [ 18 F]FAC can be deaminated in vivo by cytidine deaminase [128,129]. The biodistribution data in C57/BL6 mice showed that there is a preferential retention in high dCK-expressing tissue, such as lymphocytes, bonemarrow cells and enterocytes.…”
Section: Dckmentioning
confidence: 99%
“…The tracer was produced with high chemical and radiochemical purity with late-stage radio-fluorination of the pyrimidine. However, [ 18 F]FAC can be deaminated in vivo by cytidine deaminase [128,129]. The biodistribution data in C57/BL6 mice showed that there is a preferential retention in high dCK-expressing tissue, such as lymphocytes, bonemarrow cells and enterocytes.…”
Section: Dckmentioning
confidence: 99%
“…Positron emission tomography [ 17 ] and hyperpolarized metabolic imaging [ 18 ] have already been evaluated in EAE to monitor metabolic changes in the CNS. Still, their widespread use is restricted by the need of specialized equipment to generate the tracers along with their short half-life [ 19 ]. Magnetic resonance spectroscopy (MRS) can detect many of these metabolites without the use of a tracer, but its low sensitivity and low spatial resolution limit its application [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Building on our previous experience of 18 F-radiolabelling of nucleosides for PET imaging [14,15], we set out to apply our technology to the ProTide field. Here we report the first radiosynthetic routes to both 3 -and 2 -fluorinated model ProTides.…”
Section: Introductionmentioning
confidence: 99%